The fitness of copings constructed over UCLA abutments and the implant, constructed by different techniques: casting and casting with laser welding - Costa, Elza Maria Valadares da [UNESP]; Hoçoya, Luciana Satie [UNESP]; Bottino, Marco Antônio [UNESP] (Journal of Applied Oral Science: Revista Fob, 2004)
The alternative for the reposition of a missing tooth is the osteointegrated implant being the passive adaptation between the prosthodontic structure and the implant a significant factor for the success of this experiment, a comparative study was done between the two methods for confectioning a single prosthodontic supported by an implant. To do so a screwed implant with a diameter of 3.75mm and a length of 10.0mm (3i Implant innovations, Brasil) was positioned in the middle of a resin block and over it we screwed 15 UCLA abutments shaped and anti-rotationable (137CNB, Conexão Sistemas de Próteses, Brasil) with a torque of 20N.cm without any laboratorial procedure (control group — CTRLG). From a silicon model 15 UCLA-type calcinatable compounds (56CNB, Conexão Sistemas de Próteses, Brasil) were screwed (20 N.cm), received a standard waxing (plain buccal surface) and were cast in titanium (casting group — CG) and other 15 compounds, UCLA - type shaped in titanium (137 CNB, Conexão Sistemas de Próteses, Brasil) received the same standard waxing. These last copings were cast in titanium separated from each other and were laser-welded to the respective abutments on their border (Laser-welding group — LWG). The border adaptation was observed in the implant/compound interface, under measurement microscope, on the y axis, in 4 vestibular, lingual, mesial and distal referential points previously marked on the block. The arithmetical means were obtained and an exploratory data analysis was performed to determine the most appropriate statistical test. Descriptive statistics data (µm) for Control (mean±standard deviation: 13.50 ± 21.80; median 0.00), for Casting (36.20±12.60; 37.00), for Laser (10.50 ±12.90; 3.00) were submitted to Kruskal-Wallis ANOVA, a = 5%. Results test showed that distorsion median values differ statistically (kw = 17.40; df =2; p = 0.001<0.05). Dunn's (5%) test show difference between Casting and the two others. Conclusion: on the y axis, the smallest distortion values were obtained by the laser welding group.

A reposição de um elemento dentário pode ser feita por um implante osseointegrado sendo que a adaptação passiva de sua estrutura protética é um fator relevante para o sucesso deste trabalho. Um estudo comparativo foi feito entre dois métodos de confecção de prótese unitária suportada por implante. Para tanto incluímos no centro de um bloco de resina um implante rosqueado de 3.75mm de diâmetro por 10.0mm de comprimento (3i Implant innovations, Brasil) e sobre este parafusamos com torque de 20N.cm 15 pilares UCLA torneados anti-rotacionais (137CNB, Conexão Sistemas de Próteses, Brasil) sem qualquer procedimento laboratorial (grupo controle - GC). A partir de um molde de silicone, 15 componentes tipo UCLA calcináveis (56CNB, Conexão Sistemas de Próteses, Brasil) foi parafusado (20N.cm) ao implante e receberam enceramentos padrão (face vestibular plana) os quais foram fundidos em titânio (grupo fundição - GF). 15 componentes, tipo UCLA torneados em titânio (137CNB, Conexão, Sistemas de Próteses, Brasil) receberam o mesmo enceramento padrão e estes copings foram fundidos em titânio separados e soldados a laser aos respectivos pilares em seu bordo (grupo soldagem a laser- GSL). A adaptação marginal foi observada na interface implante/componente, sob microscópio de medição, no eixo y, em 4 pontos de referência na vestibular, lingual, mesial e distal previamente marcados no bloco. As médias aritméticas foram obtidas e uma análise dos dados foi feita para determinar o teste estatístico mais apropriado. Os dados estatísticos descritivos (µm) para Controle (média ± desvio padrão:13.50 ± 21.80; mediana 0.00), for Fundição (36.20 ± 12.60; 37.00), para Laser (10.50 ± 12.90; 3.00) foram submetidos ao Kruskal-Wallis ANOVA, a = 5%. Resultados: Os testes mostraram que os valores médios de distorção diferem estatisticamente (kw = 17.40; df =2; p = 0.001<0.05). O teste Dunn's (5%) mostra diferença entre Fundição e os outros dois grupos. Conclusão: No eixo y, os menores valores de distorção foram obtidos pelo grupo soldagem a laser de bordo (GSL).
Adaptação de copings de ritânio ao implante, construídos sobre pilares UCLA por duas técnicas: fundição e fundição com soldagem de bordo laser
Keywords: Titanium; Dental implant; Laser welding; Titânio; Implante dentário; Soldagem